1993
DOI: 10.1007/bf00157393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital abnormalities in Turkish school children

Abstract: 19750 school children, ages 6 to 15 years, were examined by the authors of this study, 1,220 (6.18%) had congenital abnormalities. In this group, 4.23% were boys and 1.88% were girls. Case histories revealed inbreeding amongst the parents (families) of children with congenital malformation to be 8.9% and 8.2% for the rest of the families in this study. There were 27 different congenital abnormalities identified, with prevalence rates of 0.05/1,000 to 15.85/1,000. The most prevalent abnormalities were umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 21 publications
6
31
2
3
Order By: Relevance
“…practice was 1.2 in 1000. The girl:boy ratio of 1:1 in this series is not the same as that reported elsewhere, 5,6,8 but the mean age of 15 (range 12-19) years was similar.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…practice was 1.2 in 1000. The girl:boy ratio of 1:1 in this series is not the same as that reported elsewhere, 5,6,8 but the mean age of 15 (range 12-19) years was similar.…”
Section: Discussionsupporting
confidence: 57%
“…practice was 1.2 in 1000. The girl:boy ratio of 1:1 in this series is not the same as that reported elsewhere, 5,6,8 but the mean age of 15 (range 12-19) years was similar.There is nothing written about this disease in the Gray and Skandalakis textbook Embryology for surgeons. 16 It has been assumed that this disease is caused by hair in the coccygeal region being "in-driven" 12 into the subcutaneous tissues, subsequently becoming infected in many cases.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Pilonidal sinus disease is a pathology most seen in young adults and generally affects boys three times more often than girls [18]. The girl:boy ratio of 5:1 in this series is not the same as that reported elsewhere [19][20][21], but the mean age of 15.21 ± 2.8 (12-18) years was similar. Although the best treatment approach for pilonidal sinus disease has not yet been established, several treatment procedures such as primary excision with or without closure, marsupialization or different flap techniques have been proposed [22].…”
Section: Discussioncontrasting
confidence: 47%
“…Therefore, the diagnosis and incidence of retractile testicle are unclear in spite of many studies. The frequency of retractile testicle in our country was found to be 0.22-3.9% (19,22,25). In our study, the frequency of retractile testicle was found to be 0,4% and the frequency of testicle with high scrotal localization was found to be 0.2%.…”
Section: Discussionsupporting
confidence: 47%